Acute gastric injury after ingestion of substrate with hyperosmolar glucose and benzoate inversely related with small intestinal bacterial overgrowth - Kim, Yeon Ji; Paik, Chang Nyol; Lee, Ji-Min; Kim, Dae Bum; Yang, Jin Mo (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The occurrence of gastrointestinal symptoms and the presence of small intestinal bacterial overgrowth (SIBO) could be determined after ingestion of substrate with highly concentrated glucose for glucose breath test (GBT), after which endoscopic images have not been clarified as well. The aims were to investigate the prevalence and relationship of acute gastric injury with SIBO after GBT. Materials and Methods: A cohort of 235 patients with functional gastrointestinal symptoms undergoing breath test with 50g glucose solution, immediately followed by upper endoscopy were surveyed. The acute gastric injury in endoscopic images and the GBT for hydrogen (H2) or methane (CH4) were assessed. Results: The prevalence of acute gastric injury was 28.1% (66/235) after GBT. There were significant differences in GBT positivity (+) with and without gastric injury (25.8% vs. 40.8%, p=0.03). In subtypes, GBT (H2) + was significantly lower in group with gastric injury than in group without. No differences were seen in GBT (CH4) + between two groups. On multivariate analysis, the subtype of GBT (H2) + (Odds ratio (OR), 0.42; 95% Confidence interval (CI), 0.20-0.90; p=0.03) inversely, and female (OR, 2.11; 95% CI, 1.11-4.00; p=0.02) were significantly related with gastric injury. Whereas, gastric injury was the only independent related factor for GBT +, inversely (OR, 0.51; 95% CI, 0.27-0.97; p=0.04). Conclusion: A highly concentrated glucose might provoke acute gastric injury, which could predict the absence of SIBO.